2012
DOI: 10.5114/aoms.2012.31296
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of obesity in children aged 6-12 years in Greece: nutritional behaviour and physical activity

Abstract: IntroductionDuring the last two decades, obesity has proved to be one of the most important problems of public health, and it is considerably more frequent in developed countries, not only in adults, but in children, too. The aim of the current study is to evaluate the prevalence of overweight and obesity in children.Material and methodsTwo thousand three hundred and seventy-four pupils in primary education were considered for the study (1206 boys and 1168 girls).ResultsIn the population-based study, the propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
33
1
8

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 47 publications
(37 reference statements)
3
33
1
8
Order By: Relevance
“…Comparing the present results with those of previous studies conducted in Greece, it was revealed that the current obesity rate of 7.4% was almost identical to that of 7.3% indicated by Kyriazis et al 47 and within the range of prevalence (5.8%-11.7%), reported in other studies. 45,48,49,51,52,60 Considering overweight and obesity prevalence as a whole, the present findings regarding pre-school aged children (24%) are slightly higher than those of previous studies.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Comparing the present results with those of previous studies conducted in Greece, it was revealed that the current obesity rate of 7.4% was almost identical to that of 7.3% indicated by Kyriazis et al 47 and within the range of prevalence (5.8%-11.7%), reported in other studies. 45,48,49,51,52,60 Considering overweight and obesity prevalence as a whole, the present findings regarding pre-school aged children (24%) are slightly higher than those of previous studies.…”
Section: Discussionsupporting
confidence: 77%
“…To our knowledge, there are only three studies focusing on pre-school children (one of them, published in two papers), that report high percentage (21.2-23.2%) of overweight (including obesity). 19,23,45,46 As far as older Greek children are concerned, prevalence of overweight (including obesity) among 6-to 12-year-olds was found to be 31.2% 47 and among 8-to 9-year-olds ranged from 30% 48,49 to 38.3 %. 50 Moreover, a higher percentage (40%) was found in 10-to 12-year-old Greeks.…”
mentioning
confidence: 99%
“…Both in the United States 7 and in Greece, 24 the prevalence of obesity was significantly higher among children and adolescents who skipped breakfast compared to those who had breakfast whereas, in Brazil, 25 breakfast was reversely associated with excess weight. Among students in our study, girls accounted for 40.7% of those who skipped breakfast and 54.7% of boys were overweight or obese.…”
Section: Discussionmentioning
confidence: 98%
“…Published data have documented that there is severe obesity problem in children in Cyprus over the past decade, making childhood obesity one of the most crucial public health problems in our country [41]. In a recent study conducted in 2010, 20.1% of Cypriot children between the ages of 6-12 were found obese, up from 16.5%…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is a global health epidemic characterized by excessive body fat accumulation [20]. Individuals with body mass index (BMI) falling within 25-29.9kg/m 2 are indicated as overweight, whereas individuals with BMI at or above 30kg/m 2 are indicated as obese [41].…”
Section: Introductionmentioning
confidence: 99%